International Refugee Law I: Migration Law vs. Refugee Law International and EU Law Perspectives - Crișan , Eugen-Gheorghe (International Criminal Law, Humanitarian Law and Refugee Law From The Perspective of Human Rights Law, 2026)
International Refugee Law is the totality of all documents and normative acts regulating the special situation of refugees at international, regional or continental level. As such, it can be found within the European Union. Refugee law is not a distinct right, separate from migration law, but rather an integral part of it which is supported by the fact that migration and refugee issues are often dealt with together. Given the situations faced by mankind and the need to provide the most appropriate regulation possible for situations of populations being forced to leave their territory, both international law and existing EU law in this area are becoming increasingly consistent, as demonstrated by the weak form of previous documents when compared with the complexity of the more recent ones. International migration law and refugee law applies to people who have had to move from one territory to another for various reasons, and find themselves in a vulnerable situation where their fundamental rights and freedoms are affected and they need protection through concrete and effective measures. Although at a cursory glance it could be argued that the term refugee is totally different from the term migrant, in reality this is not the case; a refugee is a person who migrates for certain reasons, and therefore conceptually the term refugee is contained in the term migrant or, in other words, a refugee is a migrant who leaves his or her territory because of persecution. In addition to refugees, there are other vulnerable persons in need of protection, such as persons suffering serious harm and in need of subsidiary protection, stateless persons, but also internally displaced populations, some of which do not benefit from adequate rules.Keywords: protection, migrants, refugees, persons suffering serious harm, stateless persons, internally displaced populations